2023
DOI: 10.1186/s12889-023-15673-0
|View full text |Cite
|
Sign up to set email alerts
|

Record linkage studies of drug-related deaths among adults who were released from prison to the community: a scoping review

Abstract: Background There are public health concerns about an increased risk of mortality after release from prison. The objectives of this scoping review were to investigate, map and summarise evidence from record linkage studies about drug-related deaths among former adult prisoners. Methods MEDLINE, EMBASE, PsychINFO and Web of Science were searched for studies (January 2011- September 2021) using keywords/index headings. Two authors independently screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…This makes the cohort population younger and healthier than the Canadian population. Substance use harm events occurring in correctional settings and following release are well documented and particularly prevalent immediately following release, [36][37][38][39][40][41][42][43][44][45] when many individuals are without an address or are residing in a group home so are not likely to be included with CanCHEC data. A recent scoping review also suggests that prescription misuse is a growing concern among older adults in Canada, 46 suggesting that harm events in nursing homes may also be missed in the CanCHEC data.…”
Section: Strengths and Limitations Of Canchecs In Constructing Substa...mentioning
confidence: 99%
“…This makes the cohort population younger and healthier than the Canadian population. Substance use harm events occurring in correctional settings and following release are well documented and particularly prevalent immediately following release, [36][37][38][39][40][41][42][43][44][45] when many individuals are without an address or are residing in a group home so are not likely to be included with CanCHEC data. A recent scoping review also suggests that prescription misuse is a growing concern among older adults in Canada, 46 suggesting that harm events in nursing homes may also be missed in the CanCHEC data.…”
Section: Strengths and Limitations Of Canchecs In Constructing Substa...mentioning
confidence: 99%
“…Some of these touchpoints have been previously recognized as opportunities for delivering prevention services [25,46,47]. For example, the time window following a prison release has been identified as a particularly critical and risky period, making this touchpoint a highly specific and valuable opportunity for administering prevention services [48][49][50]. However, effectively sharing these data insights with OFRs remains a challenge.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Among a cohort of men released from prison (with histories of injecting drug use), a prospective study reported high levels of unemployment, homelessness, physical and mental health morbidities, and illicit substance use during the two year follow up period [12]. Following the release from prison, individuals are at a higher risk of morbidity and mortality [13][14][15][16]. A recent scoping review (2011-2021) found that former prisoners have an increased risk of drug-related death during the first year after release from prison, with this risk particularly elevated in the first two weeks post-release [16].…”
Section: Introductionmentioning
confidence: 99%
“…Following the release from prison, individuals are at a higher risk of morbidity and mortality [13][14][15][16]. A recent scoping review (2011-2021) found that former prisoners have an increased risk of drug-related death during the first year after release from prison, with this risk particularly elevated in the first two weeks post-release [16]. Increasingly, research findings are pointing to an increased risk of hospitalisation after prison release.…”
Section: Introductionmentioning
confidence: 99%